Improving Static Balance Skills in Elementary School Children Using Themed Balance Exercises - Fenna Fauziah; Ricky Wibowo; Mesa Rahmi Stephani (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to improve balance skills in children by using themed balance exercises. This study used an experimental method of one group pre-test and post-test design. The population of this study were elementary school students in one of the elementary schools in Bandung with the ages of twelve years old.  The sampling technique in this study used purposive sampling with certain considerations, selected 25 students who were in the category of moderate and low balance skills. The measuring instrument to measure the level of balance of children using the flamingo balance test. After the intervention of themed balance training for 12 meetings with 4 meetings a week, the data were analysed using the dependent T test. The results showed that children's static balance skills improved significantly after provided with themed balance exercises for 12 meetings. Themed balance exercises provide a variety of fun balance movement exercises that are expected appropriate for twelve-year-old children.